Pemanfaatan Media Informasi Digital Pada Yayasan Sosial Graha Yatim dan Dhu’afa Jakarta Pusat - Maharani Imran (Universitas Persada Indonesia YAI, 2023)
The Graha Yatim and Dhu'afa social foundations in Central Jakarta rely on sources of funds from the community to meet the needs of educational expenses, etc., so they need information media for donors. The purpose of this non-profit activity is to provide support to the managers of the Graha Yatim and Dhu'afa social foundations in Central Jakarta in creating e-newsletters. This support is provided through lectures and practical exercises. This activity was welcomed by the administrators and orphanage children and resulted in an interesting and informative e-newsletter that is distributed to the broader community. The results of this research suggest that the orphanage caretakers can continue the creation of this e-newsletter and disseminate it through social media.